PROSPECTS FOR IMPLEMENTING DIGITAL BANKING SYSTEM IN UZBEKISTAN - Seitmuratov Yerpolat Berdakh ogly (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract : This article examines the prospects for the development of digital banking in Uzbekistan. Particular attention is paid to the current state of the banking sector, the impact of digitalization on the country’s financial system and the key benefits of introducing digital technologies. It also analyzes the challenges that banks and the state may face, as well as opportunities for improving financial inclusion, increasing transparency and efficiency of banking operations. In conclusion, possible directions for the development of digital banking and its role in the sustainable economic growth of Uzbekistan are discussed.